SANKSI HUKUM DI BIDANG PERPAJAKAN - BAMBANG ALI KUSUMO (Wacana Hukum, 2009)
Abstract:Law sanctions in taxation consist of administrative and penal sanction. However, administrative one is preferred in its implementation. It is because of its more advantage in term of time and the penal money goes to state cash. The disadvantageous is it does not give up giving to its doers and who will do it. Keywords: tax, administrative and penal sanction.